Metaphorical representation of Russia in the political discourse of anglophone mass media - D Z Shapieva (Russian journal of linguistics: Vestnik RUDN, 2013)
The article is devoted to metaphor definition and classification. It deals with metaphorical derivation specificity in the political discourse of Anglophone mass media concerning political situation in Russia.